Geographical Information System for Telkomsel Grapari Locations for Mkios in Medan City - Suyanto Agus Irawan (Marqcha Institute, 2022)
Currently the information data about the location of Grapari Telkomsel for MKIOS in Medan City has not been inventoried in a spatial-based web information system, the mapping data for the location of Grapari Telkomsel for MKIOS are still using Microsoft Word and have not been programmed. For this reason, the authors created a solution with a Geographic Information System, which is an information system that is used to enter, process, and produce geographically or geospatially referenced data, to support decision making in a plan. In this final project, we created a Geographic Information System (GIS) for Processing Telkomsel Grapari Location Data for MKIOS in the Medan City Region. This information system will later have a visualization in the form of a web that is used to map the location of Grapari Telkomsel for MKIOS in the Medan City Region. In the development of the Telkomsel Grapari Regional Data Processing system for MKIOS in the Medan City Region, PHP and MySql programming languages ​​were used as database systems